Antidiabetic potential of Withania coagulans Dunal Flower in Streptozotacin Induced Diabetic Rats - Kitukale, M.D. (International Journal of Pharmaceutical & Biological Archive, 2017)
The present study was designed to evaluate the anti-diabetic potential of flower of Withania coagulansDunal. The dried flowers were extracted successively by methanol and water. These extract thensubjected for phytochemical screening. Animals were divided in seven groups and treated with high dose(400 mg/kg) and low dose (200 mg/kg) of methanolic and aqueous extract and compared with diabeticcontrol group. Results of diabetic study indicates that administration of methanolic and aqueous extract ofWithania coagulans Dunal daily for 28 days showed significant decrease in the blood glucose of the STZinduced diabetic rats compared to the diabetic control rats. The findings of this research suggest that themethanolic and aqueous extract of Withania coagulans Dunal flower may contains bioactive constituentswith anti-diabetic potential which can be used for the treatment of diabetes mellitus.